Gero Dolezalek. Repertorium manuscrptum veterum Codicis Iustiniani, unter Mitarbeit von Laurent Mayali - Pérez Martín, Antonio (GLOSSAE. European Journal of Legal History, 1988)
After a selected bibliography on glosses and glossators, the author sets out his aims, namely to study all the glossed manuscripts of the Code and to shed light on the development of the teaching of law between 1100 and 1300.